2017
DOI: 10.1111/rda.12926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ovarian and uterine reproductive parameters, and the ovarian mRNA and protein expression of LHR and FSHR between the prepubertal and adult female cats

Abstract: Contents This study aimed to evaluate and compare the ovarian and uterine characteristics along with the ovarian mRNA and protein expression of LHR and FSHR between the pre‐pubertal and adult female cats. The uterine horns and ovaries were collected from pre‐pubertal and adult female cats at their follicular, luteal and interoestrous stages of the oestrous cycle (n = 6/group). Endometrial and myometrial thickness, uterine gland diameter, ovarian weight and type of follicles were analysed. The mRNA and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…During prepubertal development, ovarian size progressively increased up to 31 ± 3.1 weeks of age. This is similar to a previous report in which the ovarian weight of 3‐month‐old prepubertal cats was significantly lower than that of adult cats (Mehl, Khalid, Srisuwatanasagul, Swangchan‐Uthai, & Sirivaidyapong, ). Another report in prepubertal cats stated that ovarian weight increased rapidly until 3–4 months old when the study was concluded (Uchikura, Nagano, & Hishinuma, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…During prepubertal development, ovarian size progressively increased up to 31 ± 3.1 weeks of age. This is similar to a previous report in which the ovarian weight of 3‐month‐old prepubertal cats was significantly lower than that of adult cats (Mehl, Khalid, Srisuwatanasagul, Swangchan‐Uthai, & Sirivaidyapong, ). Another report in prepubertal cats stated that ovarian weight increased rapidly until 3–4 months old when the study was concluded (Uchikura, Nagano, & Hishinuma, ).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with changes in prepubertal cows and gilts, where a positive relationship between the number of antral follicles and the size of the ovaries was found (Honaramooz et al, 2004;Lents, Cushman, & Freking, 2014). Coincident with this, histological studies in prepubertal cats stated that the increase in ovarian weight was accompanied by the increase in the number and size of antral follicles (Uchikura et al, 2010;Mehl et al, 2017). In adult mammals, it has been postulated that numerous follicles are present in the ovaries at all times and the follicles destined to ovulate begin to enlarge about mid-cycle, showing a sudden enlargement just after the onset of heat (Evans, 2003).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These structures may correspond to early antral follicles, which have been histologically described in the feline ovary throughout the estrous cycle. 36,37 In all these queens, >1 mm antral follicles were ultrasonographically detected on AE5.…”
Section: Discussionmentioning
confidence: 90%
“…In ovarian follicles in the early antral period, the FSHR expression is restricted to the granulosa cells, while LHR is expressed in theca cells but also granulosa cells of large follicles (>800 µm in diameter) and CLs [74,75]. When comparing prepubertal and adult cats, no differences are observed in the ovarian gene expression of FSHR and LHR or the LHR protein.…”
Section: Ovarymentioning
confidence: 92%